Literatura polska 1918–2018. Narracje, dyskursy, dzieła - Pasterska, Jolanta; Uliasz, Stanisław (Tematy i Konteksty, 2018)
The year when the eighth number of “Themes and Contexts” is published, is unique because we celebrate the 100th anniversary of the restoration of Poland’s sovereignty. It is also an opportunity to look at the contractual century of the “new” Polish literature. In this context of “duration and changeability”, it is important to discuss the work of outstanding poets and writers of the last century, as well as interpretations of important works. This is a convenient time both for reappraisals and for new interpretations seen from a variable, literary perspective. Thinking about Polish literature in 1918-2018, we had in mind the attempts to establish the hierarchy of the most important literary phenomena in the context of political, constitutional and transformational changes. These issues are discussed in the first group of texts entitled Synthesis and reappraisals. Another group of problems connected with the subject of (Post)modern reading introduces the circle of detailed considerations. The research of Polish literature of the last century is conducted by the authors in two ways. In the first one, the researchers adopted a comparative perspective and analyzed new works compiled with works from the interwar period. The second variant is dominated by the synchronous perspective, in which the authors’ attention is focused on the originality of the latest works and contemporary methodologies of studying a literary work and “modern” contexts (social-media, pop-culture, hyper-text, blogosphere, etc.). The study of contemporary literature in the context of the works of the past century has resulted in interesting literary and cultural findings. This section, titled Views, is a voice of researchers asking for the restoration of forgotten literary writings, artists (Gniatczyński), single works. The articles collected in the volume authorize the conclusion that these conventional chronological frames cover many literary phenomena, as well as the names of writers who created and create an image of Polish literature of the last century.